Sex Hormone-Binding Globulin (SHBG) Level and It’s Associated with Some Sex Hormones in Infertile Iraqi Men - Khaled S. Abd; Adnan F. AL-Azzawie (International Journal for Research in Applied Sciences and Biotechnology, 2021)
This study aims to assessment of Sex hormone-binding globulin (SHBG) level and it’s associated with some sex hormones such as Follicle stimulating hormone (FSH), Luteinizing hormone (LH), prolactin and testosterone hormone and the infertility type in some infertile Iraqi men. Blood and seminal fluid samples from (60) idiopathic male infertile and (60) healthful individuals as a control group aged (18 to 60 year) were collected from private clinics. Serum hormones (SHBG, FSH, LH, prolactin and testosterone) were measurement using Enzyme Linked Immunosorbent Assay (ELISA). The SHBG, FSH, LH and prolactin levels were significantly higher (P≤0.01) expect of the testosterone level was significantly decreased (P≤ 0.01) in the infertile men compared with control group. High significant differences (P≤0.01) were recorded when comparing the hormonal levels (SHBG, FSH, LH, prolactin and testosterone) according to the age groups. There are significant differences (P≤ 0.01) in levels of (SHBG, FSH, LH, prolactin and testosterone) in the infertility period. Smoker infertile men have high levels (P≤ 0.05) in the SHBG and LH while have low levels in the prolactin hormones compared with control. Patients with family history have shown significant differences (P≤0.05) in the levels of DHEA-S, FSH, LH and prolactin. In conclusion, this study revealed significantly increase in the SHBG levels in the infertile men and negative correlation between SHBG and Testosterone. Therefore, SHBG has important role in the diagnosis and follow up of the male infertility.